Behind the big house : reconciling slavery, race, and heritage in the U.S. South - Skipper, Jodi (Humanities and public life., 2022)
"When residents and tourists visit plantation sites, whose stories are told? All too often the lives of slaveowners are centered, obscuring the lives of enslaved people and making it impossible for their descendants to process the meanings of these sites. Behind the Big House gives readers a candid, behind the scenes look at what it really takes to interpret the difficult history of slavery in the U.S. South. The book explores Jodi Skipper's eight-year collaboration with the Behind the Big House program, a community-based model used at local historic sites around the country to address slavery in the collective narrative of U.S. history and culture. Part memoir and part ethnography, the book interweaves Skipper's experiences as a Black woman and a southerner to imagine more sustainable and healthy spaces for interracial collaborations around historic preservation and slavery tourism in the U.S. South. Skipper considers the growing need among professional and lay communities to address slavery and its impacts through interpretations of local historic sites. In laying out her experiences through an autoethnographic approach, Skipper seeks to help other activist scholars of color negotiate the nuances of place, the academic public sphere, and its ambiguous systems of reward, recognition, and evaluation. By directly speaking to a failed integration of teaching, research, and service as a crisis in academia, she strives not to give others answers, but to model another way of being"--